Análisis de la situación política y económica de los subsidios a los combustibles del sector automotriz en Ecuador durante el periodo 2024, mediante técnicas de investigación para establecer estrategias de focalización, con el fin de alcanzar una eficiente redistribución de los recursos - Díaz Calva, Paúl Ricardo (2024)
Ecuador faces a serious challenge with fuel subsidies, which have historically accounted for about 3% of GDP and 22% of oil export revenues, generating high fiscal costs and exacerbating socioeconomic inequalities, and contributing to problems such as smuggling and negative environmental impact. Therefore, the main objective of this research was to analyze the political and economic situation of fuel subsidies in the automotive sector in Ecuador during 2024, employing research techniques to develop targeting strategies that ensure an efficient redistribution of resources. The methodology combined qualitative and quantitative approaches: a literature review was carried out to study the historical evolution of subsidies, and tools such as PESTEL, SWOT and CAME were used to assess the current situation. The study design was documentary and descriptive with a quasi-experimental component, using data from secondary sources organized and analyzed with Microsoft Excel to present results through graphs and tables. The findings indicated that subsidies for Super gasoline and diesel were high in the 1990s and 2000s, with a notable increase between 2008 and 2011, followed by gradual reductions since 2015, culminating in a near-total elimination in 2024 due to fiscal adjustments. Finally, it is concluded that, although these subsidies offered social stability and reduced the cost of living for low-income households, they also caused significant tax burdens and distorted the market.